The missing tooth mystery - Barbo, Maria S.; Duendes Del Sur (Firm); Cartoon Network (Television network) (New York : Scholastic, 2002)
Did a monster take the missing tooth? Scooby and Shaggy will solve this mystery!
"Cartoon Network."
"WB Worldwide Publishing."
"Preschool-Grade 1"--P. [4] of cover.
Keywords: Rebuses; Picture books; Scooby-Doo (Fictitious character) -- Fiction; Mystery fiction; Teeth -- Fiction